PENINGKATAN EFISIENSI LAYANAN DENGAN IMPLEMENTASI CHATBOT INTERCOM DAN SISTEM TICKETING PADA WHMCS DI PT CLOUD HOSTING INDONESIA - Naibaho, Willy Renaldi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This Reports focuses on the implementation of the Intercom chatbot and the WHMCS ticketing system at PT Cloud Hosting Indonesia, aimed at enhancing service efficiency in handling defaced websites affected by online gambling content and phishing activities. Deface is the act of damaging or altering the appearance of a webpage without the owner's permission. Typically, defacing is carried out by hackers to promote online gambling, exploit the website for other purposes, or damage the website owner's reputation. The primary goal of this research is to analyze how the integration of these tools improves response times, customer satisfaction, and incident management processes. The implementation of the Intercom chatbot automates initial customer interactions, providing instant assistance for common queries and guiding customers on steps to take in case of website compromise. The WHMCS ticketing system further streamlines the management of customer issues by enabling effective tracking, prioritization, and resolution of tickets related to defaced websites. These tools not only reduce the workload of support staff but also ensure a faster, more accurate response to critical security incidents. By examining a case study of website defacements involving online gambling and phishing content, this paper demonstrates that the combination of these tools significantly enhances the overall service efficiency, ensuring timely intervention and reducing downtime for affected websites. Additionally, the research highlights the positive impact on customer trust and satisfaction due to the improved communication and problem resolution capabilities of the system. The findings indicate that the integration of the Intercom chatbot and WHMCS ticketing system provides a scalable, automated solution for managing website security incidents, offering valuable insights for future developments in service management and security protocols at PT Cloud Hosting Indonesia